Vitamin C and the relationship with immunity and as a Preventive Agent for COVID- 19 (Sars -Cov2) (Research, Society and Development, 2021)
Vitamin C also called ascorbic acid is an antioxidant, whose function is related to the improvement of the immune system, protection against cardiovascular diseases, helps in combating stress, in addition to protection of nails, hair and eyes. Knowing its importance for immunity and taking into account its role as a disease preventive agent, the objective of this work was to carry out a bibliographic survey on the role of vitamin C in relation to immunity and how it works against COVID - 19 disease, also known like Corona virus, showing the importance of this vitamin and its mechanisms of action in the human body. From the review carried out, it was noted that vitamin C is essential for the immune system and that the lack of it leads to a disease called scurvy, in addition it was noted that ascorbic acid is found naturally in some foods, especially citrus, and it is still added in other supplements. Regarding vitamin C as a preventive agent, COVID-19 showed that patients treated with a high dose had significant improvements in both adults and children. Therefore, considering the studies carried out, it is concluded that vitamin C has that vitamin C improves the immune system and is associated with the regulation of a healthy life.